2016
DOI: 10.1088/2058-9565/1/1/015004
|View full text |Cite
|
Sign up to set email alerts
|

Simple method of generating and distributing frequency-entangled qudits

Abstract: High-dimensional, frequency-entangled photonic quantum bits (qudits for d-dimension) are promising resources for quantum information processing in an optical fiber network and can also be used to improve channel capacity and security for quantum communication. However, up to now, it is still challenging to prepare high-dimensional frequency-entangled qudits in experiments, due to technical limitations. Here we propose and experimentally implement a novel method for a simple generation of frequency-entangled qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 44 publications
0
46
0
2
Order By: Relevance
“…Not surprisingly, in the past decades there has been a steady interest in engineering quantum states of high dimensions. Many engineering strategies have been theoretically proposed and experimentally realised in quantum optical systems using a variety of degrees of freedom, from time-energy [20,21] to polarization [22], path [23], orbital angular momentum [24][25][26][27][28] and frequency [29,30]. In general, such strategies depend strongly on the specific setting under consideration and a unified framework is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, in the past decades there has been a steady interest in engineering quantum states of high dimensions. Many engineering strategies have been theoretically proposed and experimentally realised in quantum optical systems using a variety of degrees of freedom, from time-energy [20,21] to polarization [22], path [23], orbital angular momentum [24][25][26][27][28] and frequency [29,30]. In general, such strategies depend strongly on the specific setting under consideration and a unified framework is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These include encodings based on energy time [6][7][8], time bins [9][10][11][12], orbital angular momentum [13][14][15], and frequency modes [16][17][18]. Thus, highly entangled states are now routinely created in all of these platforms.…”
mentioning
confidence: 99%
“…So, it can be concluded that HOM-type multi-photon interference is a differential-frequency interference. This is true not only for the two-photon HOM interference [14][15][16], but also for the four-photon HOM interference. Therefore, positively-correlated biphotons, i.e., around ω s − ω i = 0, exhibit different patterns from the one by the uncorrelated biphotons (ω s and ω i are arbitrary) or negativelycorrelated biphotons (ω s + ω i = ω p , with ω p as the angular frequency of the pump).…”
Section: Discussionmentioning
confidence: 86%